2006
DOI: 10.2166/wst.2006.337
|View full text |Cite
|
Sign up to set email alerts
|

Fate of oestrogenic compounds and identification of oestrogenicity in a wastewater treatment process

Abstract: Understanding of the fate of oestrogen and oestrogenic compounds is important in improving the removal efficiency for oestrogens in wastewater treatment plants (WWTPs). In this study an attempt was made to clarify the fate of oestrogen, oestrogen sulphates, and oestrogenic compounds (synthetic oestrogen, nonylphenol and its relatives) by an instrumental analysis, and the fate of oestrogenicity by an in vitro assay. The investigation was conducted in an activated sludge WWTP in winter and summer, focusing on id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
19
0
4

Year Published

2007
2007
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 0 publications
2
19
0
4
Order By: Relevance
“…During winter, higher effluent concentrations for both natural and synthetic estrogens have been observed [16,71,93,94]. The reduced amount of the slow growing specified bacteria responsible for EE2 removal due to washout in winter-periods has also been cited as a factor.…”
Section: Effect Of Temperature and Rainfall On Removal Efficiencymentioning
confidence: 99%
See 2 more Smart Citations
“…During winter, higher effluent concentrations for both natural and synthetic estrogens have been observed [16,71,93,94]. The reduced amount of the slow growing specified bacteria responsible for EE2 removal due to washout in winter-periods has also been cited as a factor.…”
Section: Effect Of Temperature and Rainfall On Removal Efficiencymentioning
confidence: 99%
“…The reduced amount of the slow growing specified bacteria responsible for EE2 removal due to washout in winter-periods has also been cited as a factor. An illustration of the effects of temperature on the estrogen removals in a STW can be found in a recent study by Nakada et al [94]. A comprehensive mass balance study was carried out on a Japanese STW [94] With the available data so far no correlation between the temperature and the E2 removal in full-scale treatment plants has been found [28,72].…”
Section: Effect Of Temperature and Rainfall On Removal Efficiencymentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, a strong correlation was established between increasing temperature and decreasing conjugate concentration in the aqueous phase of activated sludge (r 2 ¼ 0.994) (Gomes et al, 2009). Temperature can influence the activity of arylsulfatase and b-glucuronidase as well as the abundance of bacteria that contain these enzymes (Liu et al, 2015;Nakada et al, 2006), which in turn affects the deconjugation of C-NEs. Table 1 shows that HRT and SRT had little correlation with the removal of C-NEs (p > 0.05), which indirectly supports that enzyme hydrolysis was a major removal pathway of C-NEs.…”
mentioning
confidence: 87%
“…An important reason for the inconsistencies is that the operational parameters, including temperature, hydraulic retention time (HRT) and sludge retention time (SRT), varied greatly among the different studies. However, studies that discussed the influence of operational parameters on the NE removal also showed significant discrepancies (Clara et al, 2005;Hashimoto et al, 2007;Liu et al, 2015;Nakada et al, 2006). It is particularly difficult to isolate the influence of one operational parameter, as the treatment processes and other operational parameters differed across these studies.…”
Section: Introductionmentioning
confidence: 99%